PENGARUH MANAJEMEN LABA DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN DENGAN KUALITAS AUDIT SEBAGAI VARIABEL PEMODERASI (Studi Pada Perusahaan Manufaktur YangTerdaftar di BEI Periode 2011-2014) - Aprih Santoso; Diana Puspitasari; Rahmatya Widyaswati (Politeknik Negeri Malang, 2017)
Management actions to perform earnings management would reduce the reliability of reported earnings, thus reducing the quality of earnings because earnings information submitted does not show the actual economic realities. The sample in this study is based on purposive sampling, with specific criteria that a manufacturing company listed on the Stock Exchange during the period 2011-2014 which publishes annual financial statements (annual report) in complete accordance with the measurement variables to be studied in this research, manufacturing company whose financial statements are audited by KAP KAP Big 4 and non-Big 4. So in the get the 22 companies audited by the Big 4 accounting firm and the 28 companies audited by non-Big 4 accounting firm. With significance level of 5% can be summed Earnings Management ( (DA) has positive effect but not significant to the Company's Performance (ROA), variable firm size (SIZE) negative effect but not significant to the Company's performance (ROA), variable Quality Audit significant positive effect strengthens the relationship between Earnings Management (DA) with the Company's performance (ROA), and variable Audit Quality significant positive effect strengthen the relationship between firm size (SIZE) with Company performance (ROA).